Attitudinal aspects of Consultants, Builders, Local People and Other Stakeholders towards Sustainable Infrastructure Development - Shrestha, Diwat Kumar; Praveen, B.M. (NPRC Journal of Multidisciplinary Research, 2025)
Sustainable infrastructure development is critical in today’s world, balancing the need for progress with the preservation of natural resources. However, the success of such initiatives largely depends on the attitudes and perceptions of key stakeholders, including consultants, builders, local communities, and government entities. This article explores these attitudinal aspects, highlighting challenges, opportunities, and strategies to align stakeholders’ perspectives with sustainable practices. The pursuit of sustainable infrastructure development has gained significant importance in Nepal, driven by increasing environmental challenges, rapid urbanization, and the need for resilient, eco-friendly systems. This study explores the attitudinal aspects of key stakeholders consultants, builders, local communities, and other entities towards sustainable infrastructure development. Consultants, as designers and planners, demonstrate a growing awareness of sustainable practices, but their efforts are often constrained by resource limitations, inadequate policy enforcement, and a lack of advanced technical training. Builders and contractors are primarily concerned with cost and time efficiency, which can lead to resistance against adopting sustainable materials and practices unless incentivized. Local communities, despite having intrinsic knowledge of their environments and a vested interest in long-term benefits, often face limited inclusion in planning processes and lack awareness about sustainable construction’s broader impact. Meanwhile, environmental organizations, government bodies, and international donors show strong advocacy for sustainability but are hampered by fragmented coordination, inconsistent policy implementation, and resource constraints. This study highlights the importance of aligning stakeholders’ attitudes and actions to achieve sustainable outcomes. It emphasizes the need for capacity building, inclusive planning, financial incentives, and stricter enforcement of sustainability policies. Addressing these attitudinal and systemic gaps can foster a collaborative environment for sustainable infrastructure development, benefiting both the environment and society at large.